INFORMATION TECHNOLOGY AS A MEANS OF INCREASING EFFICIENCY TO THE ACTIVITY OF A PHYSICS TEACHER OF DESIGN OF THE EDUCATIONAL PROCESS TICLE (Journal of Information Technologies in Education (ITE), 2012)
The article discusses issues related to the necessity of using ICT as a means of enhancing the effectiveness of a teacher of physics for the design of the educational process. Proposed list is divided into blocks of electronic resources for use during the design of the educational process.
Keywords: a teacher of physics; design of the educational process; information technology